Process model for organisational change: A study of Estonian companies - Alas, Ruth (Journal of Business Economics and Management, 2004)
Both the popular press and academic literature tend to consider organizational change as a step‐by‐step process leading to success. This paper examines the suitability of the theory that guides the implementation of change at company level for organisations in countries in transition. The author's survey, conducted in 137 Estonian companies, shows that the main focus of Estonian managers has been on initiating change and much less attention paid to assessing the process of change and making modifications and consolidating improvements. Although attention has been focused on initiating change, nobody has mentioned having identified any resistance to change. Based on the survey results the author proposes a change model for Estonian organisations.First Published Online: 14 Oct 2010